Understanding prostitutes and prostitution in democratic Burma, 1942–62: State jewels or victims of modernity? - Than, Tharaphi (South East Asia research, 2011)
Prostitution in Burmese society, as in many South East Asian countries, is a taboo subject. Unlike prostitution in countries such as Thailand, however, prostitution in Burma does not attract strong media or scholarly debate. The state and the media in Burma, during both colonial and post-colonial periods, have tended and tend to see the problem of prostitution as one of 'others'. Colonialism, a decline in morality and the corruption of women influenced by modernity or Western culture have often been portrayed as the culprits. This article analyses the Burmese terms for prostitutes and examines how prostitution was portrayed by the print media between 1942 and 1962, during which time the press was thought to have enjoyed a certain degree of freedom. Seen as a threat to the British troops during the colonial period, prostitutes were subject to controversial medical screenings; yet, seen as victims of modernity during Burma's parliamentary period (1948–62), they were often left on their own to 'resurrect' their morality.